The Need for a Model of Accompanying Family Members for Elderly with Covid-19 During Isolation at Sembiring Delitua Public Hospital North Sumatera, Indonesia to Avoid Anxiety - Herri Novita Br Tarigan; Afrizal Afrizal; Andani Eka Putra; Adang Bachtiar; Rusdiana Rusdiana (Qubahan Academic Journal)
Background: Older adults are a population more prone to anxiety when placed in isolation in hospitals because of COVID-19 exposure. This worry may jeopardize the mental well-being of senior Covid-19 patients. Aim: To preserve mental health in older individuals with Covid-19, anxiety treatment is essential. Providing support to family members during hospital isolation can help older patients overcome their fear. Methods: The investigators employed various methodologies to conduct the investigation. We developed a retrospective model because we couldn't conduct testing. The study examined isolated elderly patients who received assistance versus those who did not. Each group in the quantitative study included 11 elderly individuals, with the case group comprising 10 nurses and 11 companions. Results: The study revealed that older individuals who received support from their children during isolation experienced less anxiety compared to those who did not receive such assistance, the difference is significant. Conclusion: Older adults with Covid-19 who get support from their kids while undergoing inpatient confinement can conquer fear. To ensure effective recovery for their elderly loved ones, family members must visit, communicate with, and aid them during hospital isolation.